DCTN1-related Parkinson-plus disorder (Perry syndrome). Issue 4 (20th May 2020) - Richardson, Daniel; McEntagart, Meriel M; Isaacs, Jeremy D
Abstract : Dynactin-1 (DCTN1)-related Parkinson-plus disorder (Perry syndrome) is an autosomal dominant neurodegenerative disorder characterised by levodopa-resistant parkinsonism, weight loss, mood change and central hypoventilation. Ventilatory insufficiency is the predominant cause of death. It has been previously described in 87 people from 20 families with a worldwide distribution. It is now recognised as a distinct TDP-43 proteinopathy caused by a pathological mutation in DCTN1. Its rarity and clinical overlap with other neurodegenerative diseases increase the risk of delayed or incorrect diagnosis. Ventilatory support can improve life expectancy but this depends upon its recognition; overall its prognosis remains poor. We report a patient with DCTN1-related Parkinson-plus disorder, in whom genetic confirmation came only after death.